The Surgeon General's Facing Addiction Report: An Historic Document for Health Care. Issue 2 (April 2017) - Levy, Sharon; Seale, J. Paul; Osborne, Victoria A.; Kraemer, Kevin L.; Alford, Daniel P.; Baxter, Jeffrey; Finnell, Deborah S.; Kunins, Hillary; Walley, Alexander Y.; Lewis, David C.; MacLane-Baeder, Doreen; Gordon, Adam J.
The publication of Facing Addiction in America: The Surgeon General's Report on Alcohol, Drugs, and Health presents an historic moment not only for the field of addiction medicine, but also for the United States as a nation. The Board of Directors of the Association for Medical Education and Research in Substance Abuse (AMERSA), on behalf of our organization, would like to express our appreciation of the efforts of Dr. Vivek Murthy and the Surgeon General's Office to publish the first surgeon general's report covering substance misuse and substance use disorders.